Une proposition pour l’analyse de manuels A proposal for textbook analysis - Bittar, Marilena (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Résumé Dans les dernières années l’importance des manuels scolaires est mise en évidence dans différents pays, débouchant sur la création, en 2015, de l’International Conference on Mathematics Textbook Research and Development (ICMT). Dans ce texte, je présente une proposition pour l’analyse de manuels, constituée des étapes suivantes, non linéaires : choix des manuels ; séparation des Parties Cours et Parties Activités Proposées ; élaboration/modélisation des praxéologies mathématiques ; élaboration/modélisation des praxéologies didactiques ; croisement des donnés. Mots-clés : Manuels Scolaires, Praxéologies Mathématiques, Praxéologies Didactiques. Abstract In recent years, the importance of textbooks has been highlighted in various countries, leading to the creation in 2015 of the International Conference on Mathematics Textbook Research and Development (ICMT). In this text, I present a proposal for the analysis of textbooks, consisting of the following non-linear steps: the choice of the textbooks to be analyzed; a separation of the Course and Proposed Activities sections; the modelling of mathematical praxeology; the modelling of didactical praxeology and the cross-checking the data. Keywords: Textbooks, Mathematical Praxeology, Didactical Praxeology.